CTSA Consortium Consensus Scientific Review Committee (SRC) Working Group Report on the SRC Processes. Issue 6 (16th July 2015) - Selker, Harry P.; Buse, John B.; Califf, Robert M.; Carter, Robert; Cooper, Dan M.; Davis, Jonathan; Ford, Daniel E.; Galassetti, Pietro; Guay‐Woodford, Lisa; Huggins, Gordon S.; Kasper, Amanda; Kieburtz, Karl; et al.
Abstract: Human research projects must have a scientifically valid study design, analytic plan, and be operationally feasible in order to be successfully completed and thus to have translational impact. To ensure this, institutions that conduct clinical research should have a scientific review process prior to submission to the Institutional Review Committee (IRB). This paper reports the Clinical and Translational Science Award (CTSA) Consortium Scientific Review Committee (SRC) Consensus Working Group's proposed framework for a SRC process. Recommendations are provided for institutional support and roles of CTSAs, multisite research, criteria for selection of protocols that should be reviewed, roles of committee members, application process, and committee process. Additionally, to support the SCR process effectively, and to ensure efficiency, the Working Group recommends information technology infrastructures and evaluation metrics to determine outcomes are provided.